Spontaneous Incidence of Oncocytic Proliferative Lesions in Control Rat Kidney. (July 2014) - Hard, Gordon C.; Seely, John Curtis; Betz, Laura J.
The spontaneous incidence of foci of oncocytic proliferation (oncocytic hyperplasia and oncocytoma) was assessed in a histopathological reevaluation of the kidneys of 2, 391 male and female Fischer 344 (F344) groups of control rats from long-term carcinogenicity studies (involving 24 chemicals) that had been conducted by the National Toxicology Program. The overall incidence of oncocytic proliferation was 0.3%, with a male preponderance over females at 0.5% (6/1, 236) versus 0.09% (1/1, 155), respectively. In males, there appeared to be an association of oncocytic proliferation with advanced spontaneous chronic progressive nephropathy. Oncocytoma or oncocytic hyperplasia appear to be rare lesions in F344 rats, and observations from these carcinogenicity studies suggest that they are slow growing and tend to occur late in a rodent's life span.